2019
DOI: 10.1038/s41366-019-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microbiota-derived metabolites: a “liquid biopsy?

Abstract: Background/Objectives Non-alcoholic fatty liver disease (NAFLD) causes a wide spectrum of liver damage, from simple steatosis (SS) to cirrhosis. SS and non-alcoholic steatohepatitis (NASH) cannot be distinguished by clinical or laboratory features. Dysregulation of the gut microbiota is involved in NASH pathogenesis. The aim of this study was to assess the relationship between microbiota-derived metabolites and the degrees of NAFLD; also, to investigate whether these metabolites could be included in a panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 47 publications
3
49
0
1
Order By: Relevance
“…Moreover, the jejunal HTR expression was analyzed for the first time in women with NAFLD in the present study. In a previous work of our group, we reported that the intestine–liver axis is very important in NAFLD [ 8 ]. As stated previously, intestinal dysbiosis disrupts gut homeostasis and may affect serotonin synthesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the jejunal HTR expression was analyzed for the first time in women with NAFLD in the present study. In a previous work of our group, we reported that the intestine–liver axis is very important in NAFLD [ 8 ]. As stated previously, intestinal dysbiosis disrupts gut homeostasis and may affect serotonin synthesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the gut–liver axis plays a key role in the progression of NAFLD. Changes in the microbial composition generated by a high-fat diet (HFD) or high-carbohydrate diet (HCD) give rise to a release of metabolites derived from the microbiota that have a negative impact on liver metabolism, promoting the development of metabolic diseases such as NAFLD [ 8 ]. On the other hand, the release into the bloodstream of histamine synthesized by intestinal mast cells [ 9 ], or enterochromaffin (EC) cell-derived serotonin [ 10 ] also promote liver metabolic dysregulation, leading to steatosis and liver inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasome key protein complexes when activated induce cell apoptosis and proinflammatory cells release and are essential in host defences mechanism. NLRP3 inflammasome contributes through gut microbiota to control the NAFLD/obesity progression via overproduction of leptin, downregulation of adiponectin generation, and promotion of fibrosis [101]. Circulating microbiota-derived metabolites could be used for NAFLD diagnosis [102].…”
Section: Adipokinesmentioning
confidence: 99%
“…As expected, in the NAFLD patients, mRNA expression of fatty acid synthase (FAS, a key enzyme in the hepatic de novo lipogenesis) increased, together with the LPS receptors TLR2 and TLR4. Consequently, the circulating levels of gut microbiota-derived metabolites were analyzed observing that TMAO, glycocholic acid and deoxycholic acid plasma levels were significantly increased in NAFLD patients, suggesting the use of circulating microbiota-derived metabolites as a scoring system for the clinical diagnosis of NAFLD [45]. The up-regulation of lipogenic genes due to a high intake of saturated fatty acids (SFAs) triggers triglyceride (TG) formation [46].…”
Section: Role Of Diet In Nafld Progression and Gut Microbiota Dysbiosismentioning
confidence: 99%